THE FUTSAL DEFENSE SYSTEM MODEL FOR 14-16 YEARS OLD - Iman Sulaiman; Hernawan; lesmana (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this research is to produce a futsal defense system model for 14-16 years olds and to test the effectiveness of the futsal defense model for 14-16 years olds. The method used in this research is research and development. Data collection techniques used, interviews, tests, and field observations. The results of the product effectiveness test by comparing the two groups. the treatment group using the product development, and the control group using the pretest and posttest designs. The mean score of each group based on the test is that the effectiveness of the experimental group is higher than that of the control group. The improvement of the futsal defense system for ages 14-16 years at the time of the pre-test showed t-count = 22, 219,> t-table = 1.70329, df = 27 and p-value = 0.00 <0.005. Based on the comparison of the test results. the increase in test results for the experimental group increased significantly than that of the control group. The subjects in this study were MC Utama athletes aged 14-16 years. It is hoped that this research can provide benefits for sports practitioners, especially in the sport of futsal. Key words : Futsal, a futsal defense system model